Implementasi Metode Discovery Learning dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Hendrawati, Hendrawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to describe the implementation of Discovery Learning in learning Pancasila and Citizenship Education which has been implemented in the 2013 curriculum at SD N 07 Lasi Tuo. This study uses a case study approach to data collection techniques using interviews, observation and documentation. Analysis of the data used by applying an interactive analysis model whose stages are data collection, data reduction, data presentation and drawing conclusions. The validity of the data in this study is to use triangulation of data and data sources. The results of this study can be said that the implementation of discovery learning in Pancasila and Citizenship Education learning at SD N 07 Lasi Tuo for the 2020/2021 academic year students feel comfortable in its implementation. The results of this study also show that there is a process of elaborating concepts with this method carried out through four stages, namely as follows: data presented to students, students analyzing methods to get concepts, students analyzing methods to get concepts, students applying concepts.